1980
DOI: 10.1038/287738a0
|View full text |Cite
|
Sign up to set email alerts
|

Excretion, isolation and structure of a new phenolic constituent of female urine

Abstract: The regular occurrence of a peak due to an unidentified substance (X) in the gas chromatographic traces obtained from phenolic extracts of urine from human pregnant and non-pregnant females has been reported. The biphasic excretion of X with maxima in the luteal phase of the ovulatory cycle and relatively high levels in the first trimester of pregnancy were noteworthy and suggested that the substance may have a biological significance. Close similarities between the excretory pattern, the chemical and chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(58 citation statements)
references
References 3 publications
1
52
0
5
Order By: Relevance
“…(2005b), the total amount of ED and EL detected in urine was 40 % of the ingested dose of 500 mg SDG, the majority of which was excreted within 2 d. The residence time of enterolignans was lower in women than in men (17·3 v. 23·9 h). In earlier studies (Stitch et al 1980;Setchell et al 1981), both enantiomers of EL were detected in urine and the authors proposed that urinary EL is racaemic.…”
Section: Urinary Excretionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2005b), the total amount of ED and EL detected in urine was 40 % of the ingested dose of 500 mg SDG, the majority of which was excreted within 2 d. The residence time of enterolignans was lower in women than in men (17·3 v. 23·9 h). In earlier studies (Stitch et al 1980;Setchell et al 1981), both enantiomers of EL were detected in urine and the authors proposed that urinary EL is racaemic.…”
Section: Urinary Excretionmentioning
confidence: 99%
“…When assessing sex differences, detailed information on the menstrual cycle should be given too. Early studies showed that enterolignan excretion is associated with pregnancy and the menstrual cycle, although the number of samples analysed was limited (Setchell et al 1979;Stitch et al 1980). The possible role of progesterone detailed above would partly explain higher excretion of enterolignans during the mid-luteal phase and early pregnancy.…”
Section: Blood Levels In Relation To Bacterial Conversion Of Lignansmentioning
confidence: 99%
“…When consumed, the plant isoflavonoids and lignans undergo many metabolic conversions in the gut, which results in the formation of hormonelike compounds with estrogen activity and the ability to bind weakly to estrogen receptors (16 (17,18). Furthermore, small amounts of four plant lignans (matairesinol, lariciresinol, isolariciresinol, and secoisolariciresinol) have been identified in human urine (19,20); 7'-hydroxymatairesinol and 7'-hydroxyenterolactone were also tentatively identified in urine (21).…”
Section: Phytoestrogens Identified In Manmentioning
confidence: 99%
“…Recently, a novel compound, enterolactone (HPMF), has been isolated from human urine (65,66) (Fig. 8).…”
Section: Phytoestrogensmentioning
confidence: 99%